PENINGKATAN MINAT MEMBACA ANAK-ANAK MELALUI PROGRAM RUMAH HEBAT DI DESA SUNGAI KASAI KECAMATAN PARIAMAN SELATAN KABUPATEN PADANG PARIAMAN - Suryati Syafri; Muhammad Chalik; Tisya Aulia; Utami Mayfa Rahmania (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2024)
The reading interest among children in Sungai Kasai Village, South Pariaman, has become a primary focus in efforts to boost literacy and knowledge amidst rapid technological advancements. This community service project aims to enhance children's interest in reading through an interactive and educational reading corner, implemented through the “Rumah Hebat” program. The approach used is qualitative, involving steps such as surveying the location, researching book donation systems, developing donation brochures, collecting books, and organizing activities at “Rumah Hebat.” The program results indicate that using age-appropriate books, incorporating creative activities like story discussions, writing and drawing workshops, and educational games successfully revived children’s interest in reading. These activities provided a hands-on, engaging way for children to explore the joys of reading, which significantly contrasts with passive screen time. By offering an engaging alternative to electronic devices, the program reduced the negative impacts of technology on children, replacing screen time with reading and creative activities that foster intellectual growth. In conclusion, the “Rumah Hebat” program demonstrates that collective efforts from children, students, and the local community can positively transform children's reading habits. This initiative is expected to provide long-term benefits for the children and the Sungai Kasai Village community. For further development, it is recommended to collaborate with libraries, local authors, or art communities to offer broader access to reading materials and creative opportunities. Expanding these resources can enrich the program, providing children with diverse literary and artistic experiences, and fostering a deeper connection to reading and learning.